The Influence of Religiosity, Stress and Job Attitude towards Organizational Behavior: Evidence from Public Universities in Malaysia - Norfaizzah, Ramlee; Abdullah, Osman; Shahrul Nizam, Salahudin; Sin, Kit Yeng; Sim, Choon Ling; Muhammad, Safizal (Elsevier B.V., 2016)
The aim of the study is to investigate the influence of religiosity, stress, and job attitude on organizational behavior. The study was carried out in Malaysian setting which involved 320 respondents from public institutions. The respondents were selected through the utilization of the simple random sampling technique. The data was analyzed using SPSS ver.20 and descriptive and inferential statistics (multiple regression) were applied in the analysis. The findings of the study indicate that religiosity (β = 0.417, t = 2.442, p = 0.022 < 0.05) and job attitude (β= 0.346, t= 2.010, p = 0.05) were significantly influence organizational behavior. Based on the findings, suggestions and recommendation were forwarded.